Prenatal Androgen Excess Negatively Impacts Body Fat Distribution in a Nonhuman Primate Model of Polycystic Ovary Syndrome (PCOS) - Bruns, Cristin M (2007)
INTRODUCTION: Prenatally androgenized (PA) female rhesus monkeys share metabolic abnormalities in common with PCOS women. Early gestation exposure (E) results in insulin resistance, impaired pancreatic beta-cell function and type 2 diabetes, while late gestation exposure (L) results in supranormal insulin sensitivity that declines with increasing body mass index (BMI). OBJECTIVE: To determine whether PA females have altered body fat distribution. DESIGN: Five EPA, 5 LPA, and 5 control adult female monkeys underwent somatometrics, dual x-ray absorptiometry (DXA) and abdominal computed tomography (CT). Five control and 5 EPA females underwent an intravenous glucose tolerance test to assess the relationship between body composition and glucoregulation. RESULTS: There were no differences in age, weight, BMI, or somatometrics. LPA females had ∼20% greater DXA-determined total fat and percent body fat, as well as total and percent abdominal fat than EPA or control females (p≤0.05). LPA females also had ∼40% more CT-determined non-visceral abdominal fat than EPA or control females (p≤0.05). The volume of visceral fat was similar among the 3 groups. EPA (R(2)=0.94, p≤0.01) and LPA (R(2)=0.53, p=0.16) females had a positive relationship between visceral fat and BMI, although not significant for LPA females. Conversely, control females had a positive relationship between non-visceral fat and BMI (R(2)=0.98, p≤0.001). There was a positive relationship between basal insulin and total body (R(2)=0.95, p≤0.007), total abdominal (R(2)=0.81, p≤0.04), and visceral (R(2)=0.82, p≤0.03) fat quantities in EPA, but not control females. CONCLUSIONS: Prenatal androgenization in female rhesus monkeys induces adiposity-dependent visceral fat accumulation, and late gestation androgenization causes increased total body and non-visceral fat mass. Early gestation androgenization induces visceral fat-dependent hyperinsulinemia. The relationship between the timing of prenatal androgen exposure and body composition phenotypes in this nonhuman primate model for PCOS may provide insight into the heterogeneity of metabolic defects found in PCOS women.